2020
DOI: 10.1111/jcmm.15756
|View full text |Cite
|
Sign up to set email alerts
|

Periostin regulates autophagy through integrin α5β1 or α6β4 and an AKT‐dependent pathway in colorectal cancer cell migration

Abstract: Colorectal cancer (CRC) is the most common gastrointestinal malignancy worldwide with a remarkably high mortality rate. 1 It is the second leading cause of cancer death and over 50,000 deaths annually are estimated in the United States. 2 The prognosis of CRC is clearly related to the level of the tumour penetration through the bowel wall and the presence or absence of nodal invasion. 3 The mechanism of how CRC cells can migrate and metastasize is an active field of study. Periostin (PN) is a secreted extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…However, ITGB4 can affect EMT and tumor metastasis via different approaches in various malignancies. For instance, stimulated by periostin, it cooperates with ITGA6 as a dimer to attenuate autophagy in colorectal cancer via activating AKT signaling, which leads to EMT elevation and subsequent metastasis [ 41 ]; it directly interacted with ECM1 and enhances EMT via the FAK/SOX2/HIF-1α pathway in gastric cancer [ 21 ]; in hepatocellular carcinoma, not only does it modulate the expression of the transcriptional factor Slug to trigger metastasis but also activate the FAK/AKT pathway to accelerate epithelial cells’ transition to mesenchyme [ 23 , 25 ]; it modulates histopathological phenotypes of tumors derived from mesenchymal triple-negative breast cancer cells, affecting the metastasis [ 42 ]. In this study, ITGB4 was observed to stimulate the expression of ZEB1, one of the most significant transcription factors participating in EMT regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, ITGB4 can affect EMT and tumor metastasis via different approaches in various malignancies. For instance, stimulated by periostin, it cooperates with ITGA6 as a dimer to attenuate autophagy in colorectal cancer via activating AKT signaling, which leads to EMT elevation and subsequent metastasis [ 41 ]; it directly interacted with ECM1 and enhances EMT via the FAK/SOX2/HIF-1α pathway in gastric cancer [ 21 ]; in hepatocellular carcinoma, not only does it modulate the expression of the transcriptional factor Slug to trigger metastasis but also activate the FAK/AKT pathway to accelerate epithelial cells’ transition to mesenchyme [ 23 , 25 ]; it modulates histopathological phenotypes of tumors derived from mesenchymal triple-negative breast cancer cells, affecting the metastasis [ 42 ]. In this study, ITGB4 was observed to stimulate the expression of ZEB1, one of the most significant transcription factors participating in EMT regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Postn is expressed in tissue exposed to load, as well as in damaged tissue, and promotes cell proliferation and migration, dedifferentiation, and tissue degeneration and reconstruction by activating several signaling pathways 13 , 16 , 17 , 21 , 22 . Postn interacts with other ECM molecules and induces fibrous tissue growth to contribute to the maintenance of tissue structure 13 .…”
Section: Discussionmentioning
confidence: 99%
“…When the Akt pathway is specifically blocked, autophagy resumes. The expression of genes associated with epithelial-mesenchymal transformation was reduced [75].…”
Section: Postn Is a Cancer-promoting Molecule Of Colon Cancer Inhibit...mentioning
confidence: 99%